Correlations Between Parental Lines and Indica Hybrid Rice in Terms of Eating Quality Traits - Peng, Yan; Mao, Bigang; Zhang, Changquan; Shao, Ye; Wu, Tianhao; Hu, Liming; Hu, Yuanyi; Tang, Li; Li, Yaokui; Zhao, Bingran; Tang, Wenbang; Xiao, Yinghui (Frontiers in Nutrition, 2021)
In this study, by analysing the relationship between hybrid combinations and parental lines, we found that the eating quality traits of the hybrid combinations were determined by both parents. The sterile lines determined the overall eating quality characteristics of the hybrid combinations. For the same sterile line, there were some correlations between the hybrid combinations and restorer lines in terms of taste value, rapid visco analyser breakdown and setback values, apparent amylose content, and cooked rice hardness and stickiness. Analysis of the starch fine structure between hybrid combinations and their restorer lines demonstrated positive correlations between them in terms of short-branch amylopectin chains and amylose. Moreover, different allelic combinations of the Wx gene showed different genetic effects on the eating quality traits of hybrid rice. Overall, this study provides a framework for the development of hybrid rice with superior eating quality.